2021
DOI: 10.1371/journal.pone.0244704
|View full text |Cite
|
Sign up to set email alerts
|

Social status and previous experience in the group as predictors of welfare of sows housed in large semi-static groups

Abstract: Mixing gestating sows implies hierarchy formation and has detrimental consequences on welfare. The effects of social stress on the most vulnerable individuals may be underestimated and it is therefore important to evaluate welfare between individuals within groups. This study aimed at investigating the impact of social status and previous experience in the group on well-being of sows housed in large semi-static groups. We assessed aggression (d0 (mixing), d2, d27, d29), body lesions (d1, d26, d84) and feeding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…This is in accordance with one welfare definition 41 and showed that the clustering method may be an estimation of some components of the welfare status of an individual at a given time. However, this outcome is unexpected, considering that numerous studies have demonstrated the impact of parity on physical activity or agonistic interactions, which are variables used for the clustering 42 44 . However, the experimental design does not reveal any causal links but only potential correlations.…”
Section: Discussionmentioning
confidence: 98%
“…This is in accordance with one welfare definition 41 and showed that the clustering method may be an estimation of some components of the welfare status of an individual at a given time. However, this outcome is unexpected, considering that numerous studies have demonstrated the impact of parity on physical activity or agonistic interactions, which are variables used for the clustering 42 44 . However, the experimental design does not reveal any causal links but only potential correlations.…”
Section: Discussionmentioning
confidence: 98%
“…Транспортування, профілактика захворювань тварин та додаткові ветеринарні заходи можуть вимагати додаткових фінансових витрат. Переміщення може спричинити конфлікти через формування нових соціальних ієрархій, що також може бути стресовим фактором для тварин (Tong et al, 2020;Brajon et al, 2021).…”
Section: вступunclassified
“…As the hierarchical position of the pig in uences its behavior and interactions with conspeci cs [43], we took this information into account, hence for each group of 7, we de ned the 3 more dominant and the 3 more subordinate pigs, the remaining pig was considered intermediate. Hierarchy ranking was determined by analyzing 4 feedings prior to the baseline during the habituation period, the level of expression of both aggressive and submissive behaviors as well as the time spent eating were considered.…”
Section: Treatment Applicationmentioning
confidence: 99%